Mother’s Parenting Style, Sibling Relationship, and Learning Motivation of Youngest Child Adolescent - Ika Sri Wahyuningsih; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2017)
Learning motivation is the the driving force in adolescent to study diligently for reaching the good learning outcomes. This research aimed to analyze the influence of mother’s parenting style and sibling relationship to learning motivation of youngest child adolescent. This research was conducted in SMPN X Dramaga Bogor to sample as many as 60 youngest child adolescent (30 boys and 30 girls) aged 13-15 years. Authoritative mother's parenting style, warmth, and learning motivation on youngest child adolescent girls better than youngest child adolescent boys. Mother age and birth spacing were negatively correlations with learning motivation of youngest child adolescent while, authoritarian mother’s parenting style, authoritative mother’s parenting style, warmth and relative power were positively correlations with learning motivation of youngest child adolescent. Learning motivation influenced by mother age, authoritative mother’s parenting style, relative power, and conflict.